Attributes and trends of rentified capitalism - Giovanni Dosi; Lucrezia Fanti; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
The current phase of capitalism has been defined in many alternative ways, ranging from techno-capitalism, turbo-capitalism, unbridled capitalism, unleashed capitalism, managerial capitalism. In this paper we put forward the notion of rentified capitalism defined as a configuration of capitalism based on the progressive rentification of the socio-economic fabric acting via three mechanisms: Appropriation, Exclusion and Commodification. Delving into a classical political economy distinction of rents from a distributive versus a production perspective, we ask the following research questions: are rents simply a form of functional income source or rather a process of redefinition of property rights allowing for unjust resource accumulation? What are the attributes and trends of a rentified capitalism? How can we distinguish realms and spaces under the process of rentification? How can we measure the degree of rentification of an economy? In order to address the latter questions we identify realms and spaces of rentified capitalism (e.g., resource distribution; economic crises; finance and pseudo wealth; finance vs welfare state; housing; IPRs and Big Pharma) distinguishing countries characterised by different social and economic architectures (US, Germany, Italy) as representative of a variety of capitalisms approach. We conclude that economists are in need of a new analytical thinking advancing on the understanding of the causes and consequences of rentified capitalism.
Keywords: P1; O11; 330; Rents; political economy; modern capitalism; accumulation regime; power asymmetry